Effectiveness of Ameliorant and Potassium Fertilizer Applications on the Vegetative Growth of Sugarcane (Saccharum officinarum L.) Var. Bululawang - Boby Akbar Faris; Sudiarso Sudiarso; Nur Edy Suminarti; Subiyakto Subiyakto (Jurnal Ilmu Pertanian Indonesia, 2026)
Sugarcane (Saccharum officinarum L.) is a strategic crop in Indonesia's sugar industry, but its productivity fell from 87.40 t/ha in 2022 to 86.40 t/ha in 2023, remaining below the potential yield of the Bululawang variety (94.3 t/ha). This decline was attributed to unsustainable agriculture practices and climate change, which resulted in decreased soil fertility. The purpose of this study was to examine the effects of ameliorant and potassium fertilizer combinations on the vegetative growth of sugarcane (Bululawang variety) and identify which treatment was more beneficial. The treatments included seven combinations: P1 (no ameliorant and no K₂O), P2 (4 L/ha ameliorant + 388.8 kg K₂O), P3 (4 L/ha ameliorant + 259.2 kg K₂O), and P4 (4 L/ha ameliorant + 129.6 kg K₂O), P5 (8 L/ha + 388.8 kg K₂O/ha), P6 (8 L/ha + 259.2 kg K₂O/ha), and P7 (8 L/ha + 129.6 kg K₂O/ha) were duplicated four times. The findings revealed that the combination of ameliorant and potassium fertilizer greatly promoted vegetative development, as evidenced by increased root length, root dry weight, number of leaves, plant height, leaf area, number of tillers, stem diameter, and total plant biomass. Treatment P5 provided the highest values for several parameters, however treatment P6 had no significant difference from P5 for certain features, indicating more efficient potassium usage.Keywords: ameliorant, Bululawang Variety, potassium fertilizer, sugarcane, vegetative growth